2011
DOI: 10.1097/aog.0b013e31820563d3
|View full text |Cite
|
Sign up to set email alerts
|

One-Year Contraceptive Continuation and Pregnancy in Adolescent Girls and Women Initiating Hormonal Contraceptives

Abstract: OBJECTIVE To assess contraceptive discontinuation, switching, factors associated with method discontinuation, and pregnancy among women initiating hormonal contraceptives. METHODS This was a 12-month longitudinal cohort study of adolescent girls and women (n=1,387) aged 15 to 24 years attending public family planning clinics who did not desire pregnancy for at least 1 year and selected to initiate the patch, ring, depot medroxyprogesterone acetate, or pills. Participants completed follow-up assessments at 3,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
102
3
7

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(125 citation statements)
references
References 27 publications
9
102
3
7
Order By: Relevance
“…For instance, younger age has been extensively linked with increased DMC use [43,44,46,71,72]; however, such link was not found here. Though a critical scrutiny reveals a disproportionately small number of under 20-year-olds among respondents, the homogeneity of a university sample might also be a contributing factor; particularly since higher education has also been strongly linked with DMC [73,74].…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…For instance, younger age has been extensively linked with increased DMC use [43,44,46,71,72]; however, such link was not found here. Though a critical scrutiny reveals a disproportionately small number of under 20-year-olds among respondents, the homogeneity of a university sample might also be a contributing factor; particularly since higher education has also been strongly linked with DMC [73,74].…”
Section: Discussioncontrasting
confidence: 52%
“…In this line, DMC practice is known to be commoner in the developed world and amongst high-risk groups. In addition, individuals are known to be more likely to use DMC if they were younger [43,44]; educated [45,46]; perceived themselves at risk of STIs/pregnancies [39,47]; or perceived themselves to be selfefficacious in terms of using the methods [48,49]. Also, individuals who had relationships of recent onset or short duration [47,50], those who communicate with their partners about contraception [51,52], and those who had multiple partners [53,54] were more likely to combine methods.…”
Section: Introductionmentioning
confidence: 99%
“…En nuestra población, al igual que se refleja en otros estudios 3,12,30 , las adolescentes y jóvenes utilizan con cierta frecuencia el coitus interruptus o incluso mantienen relaciones sexuales coitales sin ningún método de prevención. Los resultados de la investigación indican que este tipo de comportamiento no siempre está asociado con EnoP y, por otra parte, con el uso de los métodos anticonceptivos considerados seguros se han registrado fallos y se produjeron embarazos no planificados.…”
Section: Discussionunclassified
“…These methods provide high levels of protection when used perfectly (0.3% failure rate), although typical use pregnancy rates are higher (9%) [7][8][9], and many women ultimately switch off of these methods [32][33][34], highlighting the importance of consistent and sustained method use. In the LARC/injectable method category, our study found a decline in injectable method use since the early 2000s.…”
Section: Discussionmentioning
confidence: 99%